Micellar catalysis of the intramolecular aminolysis of the β‐lactam antibiotic cephaclor - Oliveira, Anselmo G. [UNESP]; Nothenberg, Michael S.; Cuccovia, Iolanda M.; Chaimovich, Hernan (Wiley, 1991)
The rate of intramolecular degradation of cephaclor, involving the attack of the amino group at C‐17 (N‐18) on the β‐lactam carbonyl, was increased up to 50‐fold by neutral (polyoxyethylene‐23 lauryl ether; Brij) and zwitterionic [3‐(N‐dodecyl‐N, N‐dimethylammonium) propane 1‐sulphonate; (SDP)] micelles. The rate of OH− attack on cephaclor was increased 2–3‐fold by Brij and SDP micelles. In the absence of micelles the rate of intramolecular degradation of cephaclor increased by up to 2‐fold by addition of organic solvents. Distance calculations, based on the crystal structure of the antibiotic, showed that the intramolecular degration can only proceed in a conformation involving a cis‐amide bond (N‐14—C‐15). Micellar catalysis of the intramolecular degradation process was proposed to be due to the stabilization of the reactive conformation. Copyright © 1991 John Wiley & Sons Ltd.